العولمة الثقافية في القيم التربوية لطالبات قسم رياض الاطفال (Journal Of Educational and Psychological Researches, 2013)
Seemed reflections of cultural globalization are clear on the values of communities those values that preserve each community privacy, so that became members of these communities lack the ability to distinguish clearly between what is right and what is wrong and adoption of ideas and values imported from abroad, regardless of whether positive or negative. The aim of the research was to: - 1 - Detection of cultural globalization in the educational values for students kindergarten section. 2 - To identify the most prominent educational values (social, scientific, aesthetic, moral and spiritual) globalized culture. The current Aqtsralbges on: - Department of kindergarten students to study in the morning College for Girls, Baghdad University for the academic year 2012-2013. To achieve the objectives of the research: - The researcher prepared a measure of cultural globalization in the educational values were confirmed the veracity of the paragraphs of scale through presentation to a group of experts in this area, and extract the discriminatory power of the paragraphs of the scale and stability extracted a re Alachtbaraz way amounted reliability coefficient (0.93) After processing the data statistically research found the following results: - - The respondents believe that cultural globalization has influenced the educational values negatively.